Family, Social, and Health Workers Support with Complience Behaviour to Patients with Hypertension in Bogor, Indonesia - Siska Maytasari; Ratu Ayu Dewi Sartika (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2020)
Background: Abnormalities of the heart and blood vessels marked by an increase in blood pressure are known as hypertension. Worldwide, high blood pressure is estimated to affect more than one in three adults aged 25 years and over, or about one billion people. Overall, high-income countries have a lower prevalence of hypertension (35% of adults) than low and middle-income groups (40% of adults). The prevalence of hypertension in Indonesia based on the Basic Health Research (Riskesdas) data in 2018 was 34.1%. Objective: This study determines the relationship of family support, social support, and health worker support with compliance of hypertensive patients. Methods: This research was conducted at the Tegal Gundil Community Health Center, North Bogor District, Bogor City, Indonesia, which was conducted from May to December 2017. The design of this study was cross-sectional. Sampling was carried out with a purposive sampling method with inclusion and exclusion criteria. The former consisted of all hypertensive patients aged 25-65 years who routinely control during the last six months who are present and willing to be interviewed during the study. The later includes hypertensive patients who have memory disorders with the number of samples of 110 respondents. Results: The results showed the respondents were dominated by the age of under 59 (75.5%), female (86.4%), junior high school as the highest education (68.2%), have no job (81.8%), and the prevalence of their sufferers’ compliance was 47.3%. The results of the Chi-square test showed that family support, social environment, and health workers were associated with compliance in hypertensive patients (OR = 2.461; CI 95% 1.140 to 5.310; P Value = 0.034). Conclusion: In order to improve compliance of patients with hypertension, it is necessary to pursue a program of activities focused on health promotion activities not only for patients but also involving family and social members.